الأطر القانونية والشرعية والمهنية لتقديم صورة الرسول ﷺ في الإعلام الإسلامي - موساوي, عبد الحليم (University of Eloued جامعة الوادي, 2022)
ملخص: تسعى هذه الورقة البحثية إلى وضع تصور لمقترحات عملية لتقديم صورة الرسول صلى الله عليه وسلم في الإعلام الإسلامي، من خلال رؤية ثلاثية تتضمن شق قانوني وشرعي ومهني. وهذا كمحاولة لوضع تصور إعلامي للتعريف بسيرته العطرة وهديه الكريم في محاربة كل صور التطرف والتشدد والتزمت، عبر رسم أطر إعلامية لتقديم صورته الحقيقية ومن ثم التصدي للإعلام الغربي المضاد والرد على ما يثيرونه من شبهات وأباطيل على ديننا الإسلامي الحنيف، وما يتعرض له الرسول الكريم من إساءات متلاحقة. وستكون هذه الورقة محاولة لتقييم واقع التعاطي الإعلامي الإسلامي مع قضايا الإساءة للرسول الكريم، وهو ما سيقودنا مباشرة لمعرفة سبل تفعيل حضور سنة وسيرة الرسول صلى الله عليه وسلم عمليا من خلال استخراج كل الدرر من أقواله وأفعاله في محاربة كل صور الإهانات والإساءات التي يتعرض لها في كل مناسبة. وهذا عبر استثمار كل جوانب التأثير التي تتميز بها وسائل الاعلام التي تشهد تطورا متصاعدا وتزايد تأثيرها في ظل الانتشار الهائل لوسائل الاعلام الحديثة. وبالتالي فستكون هذه الورقة العلمية عبارة عن محاولة لتجميع جزئيات هذا الطرح عبر دراسة تحليلية شرعية، سياسية، إعلامية مركزة، وفق ما يتطلبه الموضوع، بغية التعرف على نقاط الخلل لتجاوزها ومن ثم تبني خطة علمية لتمكين الإعلام من الاهتمام بهذا الموضوع المحوري في حياة المسلم وعقيدته. Abstract: This research paper aims at setting a perception of practical proposals in order to present the image of the Prophet Mohamed PBUH in Islamic media through a tripartite vision: (legal, religious and professional). It is an attempt to develop a media perception to introduce the fragrant biography and gracious righteousness of our prophet in combating all forms of extremism, fanaticism and Puritanism. It is through drawing a media frame that can present his true image and confronting the Western counter media and responding to the suspicions and falsehoods they raise against the true Islamic religion and the successive abuses addressed to the Holy Prophet. This research paper tries also to evaluate the reality of the Islamic media's interaction towards the issues of insulting the Prophet Mohamed PBUH. In fact, this will lead us directly to find practical ways in order to activate the presence of “Sunnah and Asira Anabaouya” the prophetic biography by extracting all the pearls of his words and deeds for fighting against all forms of insults and abuse to which he is exposed to. Nevertheless, this cannot be done only by taking advantage of all the influential aspects that characterized the modern media, which are witnessing an increasing development. Its influence becomes huge with the wide spread of modern mass media. Therefore, this research paper attempts to collect all the details of this argument through an analytical, legal, political and media focused study, in order to clarify and identify the deficiencies and then adopt a scientific plan to enable the media to pay attention to this central issue in the Muslim’s life and certitude.
مقال